Characterization of a Linezolid- and Vancomycin-Resistant Streptococcus suis Isolate That Harbors optrA and vanG Operons - Du, Fanshu; Lv, Xi; Duan, Duan; Wang, Liping; Huang, Jinhu (Frontiers in Microbiology, 2019)
Linezolid and vancomycin are among the last-resort antimicrobial agents in the treatment of multidrug-resistant Gram-positive bacterial infections. Linezolid- and vancomycin-resistant (LVR) Gram-positive bacteria may pose severe threats to public health. In this study, three optrA- and vanG-positive Streptococcus suis strains were isolated from two farms of different cities. There were only 1 and 343 single-nucleotide polymorphisms in coding region (cSNPs) of HCB4 and YSJ7 to YSJ17, respectively. Mobilome analysis revealed the presence of vanG, erm(B), tet(O/W/32/O), and aadE-apt-sat4-aphA3 cluster on an integrative and conjugative element, ICESsuYSJ17, and erm(B), aphA3, aac(6′)-aph(2″), catpC194, and optrA on a prophage, ΦSsuYSJ17-3. ICESsuYSJ17 exhibited a mosaic structure and belongs to a highly prevalent and transferable ICESa2603 family of Streptococcus species. ΦSsuYSJ17-3 shared conserved backbone to a transferable prophage Φm46.1. A novel composite transposon, IS1216E-araC-optrA-hp-catpC194-IS1216E, which can be circulated as translocatable unit (TU) by IS1216E, was integrated on ΦSsuYSJ17-3. Vancomycin resistance phenotype and vanG transcription assays revealed that the vanG operon was inducible. The LVR strain YSJ17 exhibited moderate virulence in a zebrafish infection model. To our knowledge, this is the first report of LVR isolate, which is mediated by acquired resistance genes optrA and vanG operons in Gram-positive bacteria. Since S. suis has been recognized as an antimicrobial resistance reservoir in the spread of resistance genes to major streptococcal pathogens, the potential risks of disseminating of optrA and vanG from S. suis to other Streptococcus spp. are worrisome and routine surveillance should be strengthened.